2023
DOI: 10.1186/s12877-023-04113-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of real-time remote cardiac rehabilitation on exercise capacity and quality of life: a quasi-randomised controlled trial

Abstract: Background The impact of real-time remote cardiac rehabilitation (CR) on health and disability-related outcomes and its correlation with physical function are unknown. We compared the effectiveness of real-time remote CR with that of hospital-based CR on physical function improvement and physical functions of improvement (Δ) to clarify the relationship between health and disability at baseline. Methods Patients with cardiovascular diseases (CVDs) w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The rehabilitation interventions in this review showcase a remarkable range of approaches, as seen in Table 3 . Virtual reality (VR) with conventional rehabilitation therapy (CnvT), compared to CnvT plus additional therapies like iodine–bromine baths and oxygen therapy [ 21 ]; remote versus hospital-based cardiac rehabilitation (CR) [ 22 ]; the SIDERA^B program, a comprehensive telerehabilitation system that includes various forms of training such as endurance, resistance, and neuromotor training, tailored for home-based management of chronic conditions [ 23 ]; problem-solving treatment (PST) and health education (HE) via telephone [ 25 ]; use of existing healthcare system services in Taiwan [ 26 ]; robot-assisted arm training (RAT) compared to CnvT [ 27 ]; low-frequency sinusoidal sound vibration and self-care treatment [ 28 ]; diet quality modification [ 29 ]; the CaRE@Home program, with aerobic, resistance, and flexibility training, plus e-learning and health coaching [ 30 ]; functional training, bicycle exercises, and exergaming [ 32 ]; home-based resistance exercises [ 33 ]; dance classes versus kinesiotherapy [ 35 ]; powered mobility devices (PMDs); day care service with a range of medical and rehabilitative services [ 36 ]; an online psychosocial program [ 38 ]. These results reflect a broad spectrum of rehabilitation strategies and their varied impacts on different patient groups and conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rehabilitation interventions in this review showcase a remarkable range of approaches, as seen in Table 3 . Virtual reality (VR) with conventional rehabilitation therapy (CnvT), compared to CnvT plus additional therapies like iodine–bromine baths and oxygen therapy [ 21 ]; remote versus hospital-based cardiac rehabilitation (CR) [ 22 ]; the SIDERA^B program, a comprehensive telerehabilitation system that includes various forms of training such as endurance, resistance, and neuromotor training, tailored for home-based management of chronic conditions [ 23 ]; problem-solving treatment (PST) and health education (HE) via telephone [ 25 ]; use of existing healthcare system services in Taiwan [ 26 ]; robot-assisted arm training (RAT) compared to CnvT [ 27 ]; low-frequency sinusoidal sound vibration and self-care treatment [ 28 ]; diet quality modification [ 29 ]; the CaRE@Home program, with aerobic, resistance, and flexibility training, plus e-learning and health coaching [ 30 ]; functional training, bicycle exercises, and exergaming [ 32 ]; home-based resistance exercises [ 33 ]; dance classes versus kinesiotherapy [ 35 ]; powered mobility devices (PMDs); day care service with a range of medical and rehabilitative services [ 36 ]; an online psychosocial program [ 38 ]. These results reflect a broad spectrum of rehabilitation strategies and their varied impacts on different patient groups and conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, scores generally decrease (improve) after interventions and over follow-up periods, as seen in Table 3 . In some cases, the scores between the intervention group (IG) and control group (CG) are similar [ 21 ], whereas in others, there are significant differences [ 22 , 24 , 26 , 34 ]. The effectiveness of rehabilitation interventions also varies depending on the time elapsed since the intervention [ 25 , 30 , 32 , 36 , 37 , 38 ], and also with the rehabilitation intervention used [ 33 ], as seen in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to address a critical gap in existing distance rehabilitation programs, which tended to focus on aerobic exercise with a limited focus on strength training [ 2 , 6 , 7 ] In our study, we presented an intervention program specifically aimed at developing muscle endurance in low-risk cardiac patients undergoing remote rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Remote cardiac rehabilitation (RCR) has gained prominence in recent years as an effective means of enhancing physical work capacity, patient engagement, and overall satisfaction during the rehabilitation process [ 4 , 5 ]. Previous studies have consistently demonstrated its efficacy, often assessing improvements in physical work capacity through stress tests, yet with a predominant focus on aerobic exercises [ 6 ]. The traditional approach to RCR frequently quantified patient progress based on the cumulative minutes of aerobic activity per week, leaving strength training largely overlooked or underperformed [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%